PENGARUH BERBAGAI JENIS PUPUK KANDANG DAN DOSIS PUPUK UREA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI HITAM (GLYCINE SOJA L.) - Sipayung, Patricius; Hutauruk, Sixtus; Sipayung, Amsal Rosendo (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to determine the effect of various types of manure and urea fertilizer dosage on growth and production of black soybean (Glycine soja L.). The model used is a factorial Randomized Block Design (RAK) consisting of 2 factors. The first factor is the type of manure consisting of 3 levels, namely: K1 = Chicken manure (75 gr polybag-1), K2 = Goat manure (75 gr polybag-1) and K3 = Cow manure (75 gr polybag-1). The second factor is the dose of Urea fertilizer consisting of 3 levels, namely: U1 = 2.50 gr polybag-1, U2 = 3.75 gr polybag-1 and U3 = 7.50 gr polybag-1. Parameters observed consisted of plant height, number of branches, age of flowering, weight of 100 seeds, root length, number of root nodules. Based on the results of the study, it can be stated that the type of manure had no significant effect on plant height, number of branches, age of flowering, weight of 100 seeds, root length and number of root nodules of black soybean plants. The dose of urea fertilizer had no significant effect on plant height, number of branches and age of flowering, but significantly increased weight of 100 seeds, root length and number of root nodules. The interaction of type of manure and dose of urea fertilizer had no significant effect on all observed parameters.